2020
DOI: 10.1182/blood.2020006695
|View full text |Cite|
|
Sign up to set email alerts
|

Red cell–bound antibodies and transfusion requirements in hospitalized patients with COVID-19

Abstract: Berzuini et al report the observation that nearly half of patients with COVID-19 tested at their blood center had a positive direct antiglobulin test (DAT). However, eluates did not react with any test cells but did react with red cells from other patients with COVID-19 that were DAT negative. This suggests that COVID-19 may modulate the red cell membrane and present novel antigenic epitopes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 11 publications
2
77
1
6
Order By: Relevance
“…As this study represents nationwide results rather than an analysis of hospitalized patients, blood demand in the entire COVID‐19 patient population, ranging from asymptomatic individuals to patients with severe symptoms, presented lower requirements of transfusion practice. A recent study by Berzuini et al revealed greater transfusion requirements in COVID‐19 patients with direct antiglobulin test (DAT) positivity compared to those with DAT‐negative results 4 . Although the authors suggested autoimmune haemolytic anaemia as the major underlying pathomechanism for RBC transfusion, our results indicate that the transfusion demand for RBC is higher than those for other blood components possibly due to anaemia during the COVID‐19 treatment period.…”
Section: Characteristics Total No Transfusion During Covid‐19 Treacontrasting
confidence: 67%
“…As this study represents nationwide results rather than an analysis of hospitalized patients, blood demand in the entire COVID‐19 patient population, ranging from asymptomatic individuals to patients with severe symptoms, presented lower requirements of transfusion practice. A recent study by Berzuini et al revealed greater transfusion requirements in COVID‐19 patients with direct antiglobulin test (DAT) positivity compared to those with DAT‐negative results 4 . Although the authors suggested autoimmune haemolytic anaemia as the major underlying pathomechanism for RBC transfusion, our results indicate that the transfusion demand for RBC is higher than those for other blood components possibly due to anaemia during the COVID‐19 treatment period.…”
Section: Characteristics Total No Transfusion During Covid‐19 Treacontrasting
confidence: 67%
“…Most patients exhibited isolated C4d on E deposition only. Using an anti C3d for checking direct antiglobulin test (DAT) positive COVID-19 patients A. Berzuini et al detected C3 in 12% only of their patients , confirming isolated C4d deposits only in many cases (Berzuini et al, 2020), as already observed on E in kidney transplant rejection (Golocheikine et al, 2010;Haidar et al, 2012), and SLE clinical flares (Manzi et al, 2004). The decrease of CR1/E density presented here, and the detection of virus spike, C3 or C4 fragment on E (Metthew Lam et al, 2020), among COVID-19 patients, are likely to be two aspects of the same phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…It has been put forward that hospitalized COVID‐19 patients required fewer blood transfusions than other hospitalized patients [29] . Data from Italy showed that 39% of patients required transfusion (median duration of hospitalization of 15 days) for the main indication of anemia (non-bleeding), with very few patients requiring platelets or plasma [30] . If the hypothesis of an improvement in oxygen transport by transfusion has been put forward [31] , we did not find in our literature review any comparative study specifically looking at the role of treatment by increasing oxygen transport by blood transfusion in COVID-19 patients.…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%